2016
DOI: 10.1016/j.cmi.2016.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuation of echinocandin and azole treatments led to the disappearance of an FKS alteration but not azole resistance during clonal Candida glabrata persistent candidaemia

Abstract: To give an indication of a fitness cost conferred by FKS mutation-associated echinocandin resistance in Candida glabrata during human infection. Six C. glabrata clinical strains sequentially isolated from blood and a hepatic abscess in a solid organ transplant recipient were analysed. The patient had received long-term azole and echinocandin therapy for invasive aspergillosis and persistent candidaemia. Minimal inhibitory concentrations were determined by the European Committee on Antimicrobial Susceptibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 13 publications
2
5
0
Order By: Relevance
“…We also found that mixed genotypes could arise in the gut ( Tables 1 and 2 ), particularly if a phenotype (i.e., Fks2-P667T) that leads to low-level resistance (<2 μg/ml) develops. This finding is consistent with clinical studies involving serial isolates from patients with recurrent bloodstream infections that show breakthrough isolates with different FKS alleles ( 35 , 36 ). Most of our studies included colonization with the Δ msh2 mutator strain.…”
Section: Discussionsupporting
confidence: 89%
“…We also found that mixed genotypes could arise in the gut ( Tables 1 and 2 ), particularly if a phenotype (i.e., Fks2-P667T) that leads to low-level resistance (<2 μg/ml) develops. This finding is consistent with clinical studies involving serial isolates from patients with recurrent bloodstream infections that show breakthrough isolates with different FKS alleles ( 35 , 36 ). Most of our studies included colonization with the Δ msh2 mutator strain.…”
Section: Discussionsupporting
confidence: 89%
“…Nevertheless, this experiment had some limitations, as the original samples sent from the hospital could be an already isolated colony. Serial C. glabrata isolates from the same patient showing different antifungal resistance profiles due to the selective pressure induced by changes in antifungal treatment have been previously reported (Cho et al, 2015; Imbert et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…Outside of the US or Northern Europe 6 , C. glabrata is less commonly isolated 7 . Nonetheless, C. glabrata manifests an intrinsically low susceptibility to azoles in vitro or tends to easily develop azole resistance during the course of antifungal therapy 8 , 9 . Alarmingly, exposure of C. glabrata cells to an antifungal agent may lead to highly variable, “evolvable” genomes capable of quick development of resistance to multiple antifungal drug classes 10 , including triazoles ( e.g .…”
Section: Introductionmentioning
confidence: 99%